But it came from a food pantry: Product stigma and quality perceptions of food pantry offerings. (8th January 2023) - Byrne, Anne T.; Just, David R.; Barrett, Christopher B.
Abstract: Among the millions of food insecure people in high income countries, only a modest fraction uses food pantries. Stigma is commonly cited as a barrier to use and may arise due to the perceived low product quality of pantry offerings. This study tests the hypothesis that "product stigma" is present among prospective pantry clients. In an online experimental survey of low‐income respondents, we ask participants to evaluate food items under four different treatments. In a two‐by‐two randomized design, in one dimension they are told the food is from a grocery store or from a food pantry, and in the other dimension they are or are not provided with photos of the food items, in some cases indicating a popular brand. The study finds that respondents exhibit a negative perception of the quality of food from a pantry, but that perception is largely offset when they are shown an informative visual depiction of that food. The effect of brand information is explored in a second online experimental survey and found to be an important component of consumer perception, partly mitigating the product stigma effect of food pantry offerings, but less so than a photo does. Results suggest that food banks and food pantries may combat product stigma through marketing that uses photos, brand names, or both to depict the quality of the products they offer. Such interventions may encourage current users to visit more frequently and needy non‐users to visit at all.